Efek Antijamur Minyak Atsiri Jahe Putih Kecil (Zingiber officinale var. Amarum) terhadap Candida Albicans - Huanny Satriyani; Lakshmi A. Leepel; Antonia Tanzil (Faculty of Dentistry, Universitas Indonesia, 2015)
The side effects of many antifungal drugs make it necessary to find an herbal alternative with reduced side effects. Many herbals are knwon to have an antifungal effect, including ginger with its volatile oil composition. However, the specific antifungal effect and optimal concentration of the volatile oil from Zingiber officinale var. amarum against C. albicans is not yet known. This research was done to verify the antifungal effect of Zingiber officinale var. amarum volatile oil on C. albicans, to determine its optimal concentration, and to determine the relation between the volatile oil was provided by water and steam distillation of BALITTRO, Bogor. The colonies were double counted in two steps. First, the volatile oil at concentrations of 100%, 50%, 25%, 12.5%, 6.25%, 3.125%, 1.56% and 0.78% were applied for treatment, wheras in the second step concentrations of 100%, 90%, 80%, 70%, 60%, and 50% were used. In the disk diffusion method, the volatile oil concentrations of 100%, 70%, 60%, 50%, 25%, 12.5%, 6.25% and 3.125% were applied in triplicate in Petri dishes containing C. albicans by using 6 mm blank disks. Result: Mann-Whitney test showed the significant decrease of the colonies between 6.25% and 3.125% of the volatile oil concentration (α = 0.021), and also between the volatile oil concentration 6.25% and the control group (α = 0.014). The Spearman test showed a positive and strong correlation between the volatile oil of Zingiber officinale var. amarum and its inhibition zone (r = 0.91). Conclusion: The volatile oil of Zingiber officinale var. amarum has an antifungal effect against C. albicans with an optimal concentration of 6.25%, and increasing volatile oil concentration is followed by increasing inhibition zone.